Cardiac output response to exercise in patients before allogenic hematopoietic stem cell transplantation - Yoshida, Shinya; Someya, Fujiko; Yahata, Tetsutaro (International Journal of Clinical Oncology, 2018)
Introduction High-dose chemotherapy for remission induction can induce cardiac toxicity prior to hematopoietic stem cell transplantation (HSCT). However, the details of cardiac function in patients undergoing HSCT are unclear, particularly during exercise. The aim of present study was to evaluate cardiac output responses to exercise in patients after high-dose chemotherapy before HSCT compared with in age-matched healthy controls. Methods Twenty-nine patients before HSCT (age 44.6 ± 15.2 years) and 13 controls (45.8 ± 16.0 years) performed the 6-min walk test (6MWT). Cardiac output (CO), stroke volume (SV), heart rate (HR), and cardiac index (CI) were continuously measured during the 6MWT using the noninvasive thoracic impedance method. Results No significant difference was observed in the six-minute walk distance (6MD) between the two groups. SV, CO, and CI both at rest and the end of the 6MWT in the patients were significantly lower, compared with the controls, but there was no significant difference in HR. In all subjects, the 6MD was positively correlated with SV, CO, CI, and HR after the 6MWT. Conclusion These findings suggest that cardiac output response to exercise indicates exercise intolerance, which may not be detected by 6MD in patients before HSCT.